Photodynamic therapy for metastatic breast cancer - E. V. Horanskaya; M. A. Kaplan; V. N. Kapinous; E. V. Yaroslavtseva; I. S. Spichenkova; A. M. Shubina; O. V. Borgul; Ju. A. Ragulin; M. V. Taibova (Biomedical Photonics, 2014)
Results of treatment for cutaneous metastasis of breast cancer with photjdynamic therapy are represented. The study included 46 patients, the total number of treated cutaneous metastases was 535. For photodynamic therapy photosensitizer photolon given intravenously at a dose of 0.9–1.6 mg/kg body weight 3 h before treatment session (wave length 661±1 nm, плотность мощности 0,11–0,56 J/cm2), мощность на выходе волокна 0,3–2,0 Wt, light dose 50–600 J/cm2. Complete regression of metastasis was obtained in 33.6% of cases, partial – in 39.4%, stabilization – in 22.6%, progression of disease was in 4.3% of cases. The results show the perspectiveness of photodynamic therapy for metastasis as one of the step of treatment.